Caribou response to human activity: research and management - Miller, Donald R. (Rangifer, 2003)
This paper describes the need by researchers and managers of caribou (Rangifer tarandus) to carefully assess the impact of their study methods on animals and results. An error made during a study of barren-ground caribou is described. Assumptions made during preparation of study methods need to be tested during collection of data. Study plans should include communication with, and respect for, residents who depend on the caribou resource. During field observations of caribou behavior, feeding habits, rutting activity or sex and age composition, closer is not better. During capture, handling and marking activities, shorter processing time is better. During aerial surveys, photography, sex and age determinations, higher is better. When interpreting data collected from marked caribou, and generally applying to the unmarked population, caution is advised. The merits and drawbacks of helicopter use to capture and mark caribou for research and management need to be discussed.